I might be wrong but I think the answer would be -x+2x+6 as a simplified version because if you use the equation (x+4•x+3)-3x(x+1)=a (or any letter you choose), you will get 3x+x^2+12+4x-3x-3x^2=y. Then, you can combine like terms:
4x-2x+12=a
Answer: 12 pounds.
Step-by-step explanation:
To solve this question, we'll use the direct proportion which is.
y = kx
Where,
y = weight on moon = 48 pounds
x = weight on Earth = 300 pounds
k = Unknown
y = kx
48 = 300k
k = 48/300
k = 0.16
The weight that a 75 pound object on Earth would weigh on the moon will be:
y = kx
where,
y = weight on moon = Unknown
k = 0.16
x = weight on Earth = 75 pounds
y = kx
y= 0.16 × 75
y = 12 pounds
The weight on the moon will be 12 pounds.
Answer:
B. 4
Step-by-step explanation:
We are looking for the coefficient of the term x⁵. When we see it in the polynomial as 4x⁵, our coefficient and answer would then be 4.
Answer:
3Median = Mode + 2Mean
Step-by-step explanation: